ELAUTÓCRATALIBERAL. RIVAAGÜERO Y JOHN STUART MILL - Rivera, Victor (2006)
This article seeks to be a depiction of Riva Agüero's political thought.Under he scope, shelter of liberal ideas, Riva Agüero is ranked as a nonuniversalist,historicist, "contingential" and liberal philosopher. The articleenhances his standing in relation to the bases of political organizations, itssource being not a liberal social contract'but an act of ontological violence,an original co-action. Riva Agüero sems to ha ve elaborated his ownreading of J.S. Mill which puts us close to a hermeneutical ontology ofpolitical destiny .